(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: In 2022, for the first time, the Faculty of Medicine, Dai Nam University applies scientific research methods to 3rd year medical students. Objective: To evaluate the impact of the Medical Scientific Research Methods module on medical students’ skills and knowledge. Methods: This pre-test post-test pilot study used a prospective descriptive exploratory method by non-probability convenience sampling of all people participating in the course “Medical science research methods,” which was compulsory for 3rd-year medical students, Faculty of Medicine, Dai Nam University, from August to December 2022. The study invited a total of 89 students from two classes to participate. At the beginning of the course, 82 students completed the survey, while 66 students responded to the second survey after completing the course. Result: This study demonstrated that an undergraduate research methods course had a meaningful impact on medical literature search behaviors, understanding of medical research terminology, and confidence in evidence-based medical practice among students. However, despite these positive results, the knowledge and skills of students in evidence-based medicine were limited. Conclusion: The scientific research methods course has significantly improved students’ EBM knowledge and skills, albeit with some limitations. However, this study highlights the need for continued training programs and practical experience in medical research to enhance further and maintain learners’ proficiency in EBM.